INVESTIGATION ON PHYSICAL AND ELECTRICAL PROPERTIES OF THE SiO2-ZnO NANOCOMPOSITE AT DIFFERENT COMPOSITION MIXINGS - Sinol, Moh.; Rani, Erika (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2017)
Physical and electrical properties of The SiO2-ZnO mixing at different compositions were investigated. The experiment used simple mixing method at the sintering temperature 600oC. It was used the composition mixing ratio of SiO2:ZnO ie. 0:10; 7:3; 5:5; 3:7; and 10:0 (%Wt). Based on X-Ray Diffraction (XRD) results, it obtained that a new phase in each sample was not formed even though having different diffraction peak. The mixing ratio of SiO2: ZnO nanocomposite (7:3 %wt) had the biggest grain size (77,92 nm), the highest dielectric constant (3.00E+05) and the smallest conductivity (0,726549 (Ωm)-1). On the other side, the mixing ratio of SiO2: ZnO nanocomposite (5:5 %wt) had the smallest grain size (35.42nm), dielectric constant (3.00E+2) and the highest conductivity (25.36729 (Ωm)-1). It can be concluded that the difference of composition ratio offered the change on both physical and electrical properties of SiO2-ZnO nanocomposite.